Salary delays and arrears in urban councils: survival strategies for the municipality of Chitungwiza employees. - Nyakabwe, Ashley (Midlands State University, 2017)
The main thrust of this research was to analyse the survival strategies employed by Chitungwiza Municipality employees in the era of salary delays and arrears. The research was influenced and informed by the reasons behind employees’ continuation to report to work whilst they are not being remunerated consistently paying heed to how they are surviving. This study therefore sought to unearth the causes of salary delays and arrears which have crippled the Chitungwiza Municipality’s ability to remunerate timeously, the impact of salary delays and arrears on council employees and their families as well as on organizational productivity, the survival strategies employed by the unpaid employees in a bid to survive as well as how the organization can alleviate the predicament of salary delays and arrears. The second chapter of the research meant to address the above stated objectives through reviewing the relevant literature that has already been published in as far as the research study is concerned. It established that the causes of salary delays and arrears comprised of economic hardships, corruption, low revenue inflows, industrial decline and government policies, the effects of non-payment of salaries included financial effects, social effects, low productivity and brain drain, poverty, low staff morale, labour unrest, employee disenchantment and the survival strategies employed by employees consisted of income generating projects, moonlighting, borrowing, unpaid leave and fabricated leave, stealing of company hours, engaging in corrupt activities among others. The research was descriptive in nature and characterized by both quantitative and qualitative research design. The study population was limited to 250 employees and a sample of 36 participants was utilised. Simple random sampling and purposive sampling techniques were made use of. Both primary sources of data which was obtained through interviews and questionnaires and secondary which consists of scholarly journals, textbooks, newspapers and policy reports were also used in the research. The study recommends that council should conduct revenue generating projects, slash the top management’s exorbitant salaries and allowances, downsize in order to reduce the wage bill and to manage effective operations of the organization, reduce the wage bill, resort to the issue of providing vouchers, support and incorporate the informal sector, enforce strict penalties of corruption offenders. The major conclusions pointed corruption and the general poor performing national economy as the major causes of salary arrears and delays in Chitungwiza Municipality, brain drain, low staff morale and low productivity as the major effects of not remunerating employees timeously and consistently and the survival strategies employed by the unpaid employees consisted of theft, income generating projects, buying and selling among others.